Synergistic effects of surfactant-assisted ionic liquid pretreatment rice straw. (August 2016) - Chang, Ken-Lin; Chen, Xi-Mei; Han, Ye-Ju; Wang, Xiao-Qin; Potprommanee, Laddawan; Ning, Xun-an; Liu, Jing-yong; Sun, Jian; Peng, Yen-Ping; Sun, Shui-yu; Lin, Yuan-Chung
Graphical abstract: Highlights: Surfactants-assisted ionic liquid pretreatment rice straw in a single system. Surfactant increased lignin removal by 32.53% compared with IL-only pretreatment. High total reducing sugar yield was obtained with IL + 1% SDS-pretreated rice straw. IL + 1% SDS-pretreated rice straw exhibited lower cellulose crystallinity. Abstract: The aim of this work was to study an environmentally friendly method for pretreating rice straw by using 1-butyl-3-methylimidazolium chloride ([BMIM]Cl) as an ionic liquid (IL) assisted by surfactants. Different temperatures, reaction times, and surfactant concentrations were studied. Compared with [BMIM]Cl only pretreatment, the addition of 1% sodium dodecyl sulfate (SDS) and 1% cetyl trimethyl ammonium bromide (CTAB) increased lignin removal to 49.48% and 34.76%, respectively. Untreated and pretreated rice straw was thoroughly characterized through FTIR, XRD, and FE-SEM. Cellulose crystallinity and surface morphology of the rice straw were substantially altered after surfactant-assisted IL pretreatment. In conclusion, surfactant-assisted IL pretreatment is an effective method for producing fermentable sugars from lignocellulosic substrates.